Worker-Plant Matching and Ownership Change - Ragnhild Balsvik; Stefanie Haller (Center for Economic Studies and ifo Institute (CESifo), 2019)
Is ownership change an opportunity for new owners to make systematic changes in the workforce of the acquired plant? We document changes to the workforce along observable and unobservable dimensions of worker quality around ownership change using matched employer-employee data. We observe above average separations of workers around domestic acquisitions. This is associated with a decline in unobserved worker quality in the plant. Foreign acquisitions are not associated with above average worker turnover, instead new foreign owners share rents with the high skilled workers that are already in the plant before the acquisition.
Keywords: F66; F23; J20; 330; multinational firms; acquisitions; worker reallocation; unobserved fixed effects